The Mediating Role of Bullying and Victimisation on the Relationship Between Problematic Internet Use and Substance Abuse Among Adolescents in the UK: The Parent–Child Relationship as a Moderator - Samara, Muthanna; Massarwi, Adeem Ahmad; El-Asam, Aiman; Hammuda, Sara; Smith, Peter K.; Morsi, Hisham (Frontiers in Psychiatry, 2021)
Over the last decade, research into the negative effects of problematic internet use has greatly increased. The current study adopted a mediation-moderation model in exploring the relationship between problematic internet use and substance abuse (drinking, drug use and smoking tobacco cigarettes) among 1,613 adolescents (aged 10-16) in the UK. The findings of the study revealed a significant positive correlation between problematic internet use and substance abuse, which is mediated by traditional and cyber bullying and victimization. Furthermore, parent-child relationship was found as a protective factor, that moderated the correlation between problematic internet use and substance abuse, and the correlation between problematic internet use and traditional bullying. The study emphasizes the critical need to reduce problematic internet use among adolescents as a risk factor for involvement in bullying as perpetrators and victims, in addition to substance abuse. Furthermore, the findings of the study highlight the importance of a good parent-child relationship as a protective factor among adolescents. In light of the findings of the study, interventions for reducing problematic internet use taking into account bullying and the parent-child relationship are needed among adolescents.